Monitoring the dual-season hydrological dynamics of the Pong reservoir in Himachal Pradesh, India - Sarda, Rajesh; Kumar, Pankaj (Frontiers in Remote Sensing, 2025)
Reservoir hydrological conditions play a crucial role in both natural and human ecosystems. This study investigates the dual-season (pre-monsoon and post-monsoon) hydrological dynamics of the Pong Reservoir and analyzing the spatial character using Landsat multi-spectral images collected from 1994 to 2024. The 30 years were divided into three phases to assess changes in hydrological consistency and relative water depth over time. The Modified Normalized Difference Water Index (MNDWI) proved effective for mapping the water coverage area of the Pong Reservoir. Analysis based on MNDWI indices reveals significant seasonal fluctuations in water coverage, with 36.18 km2 of the reservoir exhibiting seasonal characteristics. Furthermore, the phase-wise results indicate a substantial decline in the area of high hydrological consistency during the pre-monsoon season, from 120.54 km2 in Phase 1 (1994–2004) to 88.49 km2 in Phase 3 (2015–2024). The change matrix indicates that 10.62 km2 transformed from higher to lower hydrological consistency classes from Phase 1 to Phase 2, and a further 51.97 km2 underwent a similar transformation from Phase 2 to Phase 3 in the post-monsoon season. The study employed a spatial linear trend modelling approach to identify trends in relative water depth, revealing a decreasing trend and a quantifiable reduction in the reservoir’s depth for both seasons. Additionally, further analysis was conducted on the impact of seasonal rainfall and sedimentation on the hydrological dynamics of the Pong Reservoir. These findings could assist policymakers in formulating effective conservation plans for this important Ramsar site.